Pengaruh Kompensasi, Beban Kerja, dan Stres Kerja terhadap Kinerja Karyawan pada PT Panca Boga Paramita Cabang TSM Kota Bandung - Berkam, Denis; Rahmi, Palupi Permata (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This research aims to understand the description of employee performance, compensation, workload, and work stress and analyze the influence of compensation, workload, and work stress on employee performance at PT Panca Boga Paramita, TSM Bandung City Branch. The research method used is quantitative with a descriptive and verification approach. Sampling was carried out using total or saturated sampling (census) involving all 30 PT Panca Boga Paramita, TSM Bandung City Branch employees. Data collection was carried out through distributing questionnaires. The data analysis techniques used include multiple linear regression analysis, correlation coefficient analysis, and coefficient of determination analysis. Descriptive analysis shows that employee performance at PT Panca Boga Paramita TSM Bandung Branch scores 784 in the poor category. Compensation has a score of 524 in the excellent category. Workload has a total score of 763 in the high category. Work stress has a total score of 1020 in the medium category. This research shows that compensation affects employee performance, with a correlation value of 0.690. Workload influences employee performance with a correlation value of 0.662. Work stress influences employee performance with a correlation value of 0.689. Simultaneously, compensation, workload, and work stress influence employee performance, according to the results of the simultaneous correlation test, which shows a value of 0.783 with an influence contribution of 64.2%.